Prevalence and Severity of COVID-19 and Missed Job Opportunities among Healthcare Workers in Mazandaran Province, February-June 2020 - Farhang Babamahmoodi; Ahmad Alikhani; Masoud Maboudi; Jamshid Yazdani Charati; Bita Paknezhad; Amir Hossein Gharib; Azadeh Khalatbari (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: The COVID-19 pandemic resulted in an uncontrolled disease burden on healthcare workers (HCWs) worldwide. We aimed to investigate the prevalence and severity of COVID-19 in HCWs of selected hospitals in Mazandaran province and examine the association between COVID-19 and missed opportunities of HCWs. Materials and methods: In this retrospective descriptive-analytical study, 1105 HCWs in Qaemshahr Razi Hospital and Sari Fatemeh-Zahra Hospital were studied between February 2020 and June 2020. In order to evaluate the frequency and severity of the disease, clinical and paraclinical manifestations were recorded by a trained HCW. Data were analyzed in SPSS V18. Results: The frequency of COVID-19 was 16.19% among HCWs. The patients included 113 (63.13%) nurses, 47(26.26%) service providers and administrative personnel, and 19(10.61%) physicians. Duration of sick leave was found to be significantly associated with severity of COVID-19 (P=0.006). This length was also significantly associated with the job and was longer in nurses (P=0.013). Our findings revealed a significant relationship between the level of adherence to personal protective equipment (PPE) and the severity of COVID-19 (P=0.001). Conclusion: COVID-19 could exert remarkable impact on the quality of work in HCWs, especially among nurses. Effective training of HCWs regarding PPE instructions results in suitable protection against severe forms of the disease.